Lycorine Alkaloid and Crinum americanum L. (Amaryllidaceae) Extracts Display Antifungal Activity on Clinically Relevant Candida Species - Lorene Coelho Silva (Molecules, 2022)
Candida species are the main fungal agents causing infectious conditions in hospital patients. The development of new drugs with antifungal potential, increased efficacy, and reduced toxicity is essential to face the challenge of fungal resistance to standard treatments. The aim of this study is to evaluate the in vitro antifungal effects of two crude extracts of Crinum americanum L., a rich alkaloid fraction and lycorine alkaloid, on the Candida species. As such, we used a disk diffusion susceptibility test, determined the minimum inhibitory concentration (MIC), and characterized the components of the extracts using Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (ESI FT-ICR MS). The extracts were found to have antifungal activity against various Candida species. The chemical characterization of the extracts indicated the presence of alkaloids such as lycorine and crinine. The Amaryllidaceae family has a promising antifungal potential. Furthermore, it was found that the alkaloid lycorine directly contributes to the effects that were observed for the extracts and fraction of C. americanum.